Taburnaemines A–I, Cytotoxic Vobasinyl-Iboga-Type Bisindole Alkaloids from Tabernaemontana corymbosa - Zhang, Yu (J Nat Prod, 2018)
Nineteen vobasinyl-ibogan-type bisindole alkaloids, including nine new compounds, taburnaemines A–I (1–9), were isolated from the twigs and leaves of Tabernaemontana corymbosa. The structures and absolute configurations of the new alkaloids were determined by a combination of MS, NMR, and ECD analyses. Alkaloids 1–5 contain a rare 1,3-oxazinane moiety in the vobasinyl unit, while 6 has an uncommon 1,3-oxazolidine moiety in the iboga unit. The absolute configurations of alkaloid 1 and the known alkaloid tabernaecorymbosine A (10) were confirmed by single-crystal X-ray diffraction analysis. All of the bisindole alkaloids, except 2 and 16′-decarbomethoxytabernaecorymbosine A (14), showed antiproliferative activity (IC(50) 2.6–9.8 μM) against several human cancer cell lines, including A-549, MDA-MB-231, MCF-7, KB, and P-glycoprotein-overexpressing multidrug-resistant KB cells. The preliminary structure–activity relationship correlations are also discussed.